Ngoluk Moman (Nursery Rhymes in Mising) - (:unkn) unknown (Central Institute of Indian Languages Mysore, 1995)
In this book primary section's poems is given for children. This book can be used for primary section for language learning
Keywords: Mishing; Ngoluk Moman (Nursery Rhymes in Mising); Nursery Rhymes; Mishing